Microsteatosis in Livers From Donation After Circulatory Death Donors Is Associated With Inferior Outcomes Following Liver Transplantation. Issue 9 (25th August 2020) - Bath, Natalie M.; Leverson, Glen; Al‐Adra, David P.; D'Alessandro, Anthony M.; Mezrich, Joshua D.; Foley, David P.
Abstract : The acceptable threshold remains unknown for the percentage of macrosteatosis (MaS) and microsteatosis (MiS) to yield optimal outcomes after donation after circulatory death (DCD) liver transplantation (LT). The purpose of this analysis was to determine the impact of donor liver MaS and MiS on DCD LT outcomes. Using the Organ Procurement and Transplantation Network database, we analyzed pretransplant biopsy results from adult, solitary, DCD livers transplanted between January 1, 2006, and December 31, 2017. Kaplan‐Meier analysis was used to assess graft and patient survival based on MaS and MiS severity. MiS was divided into the groups MiS ≤10% and >10%. MaS was divided into the groups MaS ≤15% and >15%. Of 7757 recovered DCD livers, 11.4% (n = 885) were biopsied and transplanted. Patients who received DCD livers with MaS >15% had significantly worse patient survival ( P < 0.04), and those with MiS >10% demonstrated inferior graft and patient survival ( P < 0.02). In multivariate analyses including known risk factors, both MaS >15% and MiS >10% were associated with increased risk of graft failure and patient mortality ( P < 0.03). Recipient and donor age >60 years were also associated with increased risk of graft failure and patient death. This analysis demonstrates that MaS >15% and MiS >10% are additional risk factors for graft loss and patient mortality in DCD LT.